2021
DOI: 10.3389/fvets.2021.659244
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Glaesserella parasuis Virulence in Mice and Piglets

Abstract: In this study, we compared the virulence of the most common serovars of Glaesserella parasuis in China, serovars 4, 5, 12, and 13 (36 strains in total) in BALB/c mice and piglets. In mice, the median lethal doses (LD50s) of the four serovars were roughly 9.80 × 107–4.60 × 109 CFU, 2.10 × 108–8.85 × 109 CFU, 4.81 × 107–7.01 × 109 CFU, and 1.75 × 108–8.45 × 108 CFU, respectively. Serovar 13 showed the strongest virulence, followed by serovar 4, serovar 12, and serovar 5, but a significant difference in virulence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Although single infections with bacteria or viruses alone can induce respiratory infections in pigs, coinfection with various pathogens is very common [ 28 , 71 ]. A Gps infection initiates an innate immune response and induces the production of inflammatory cytokines [ 72 , 73 ]. HP-PRRSV2 targets the immune system of pigs, impairing immune defense against pathogenic microbes and increasing host susceptibility to primary and secondary pathogens [ 64 , 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although single infections with bacteria or viruses alone can induce respiratory infections in pigs, coinfection with various pathogens is very common [ 28 , 71 ]. A Gps infection initiates an innate immune response and induces the production of inflammatory cytokines [ 72 , 73 ]. HP-PRRSV2 targets the immune system of pigs, impairing immune defense against pathogenic microbes and increasing host susceptibility to primary and secondary pathogens [ 64 , 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…BALB/c mice and RAW264.7 cells are the common and convenient models for studying PCV2 infection [27,33]. Despite BALB/c mice being regarded as an inadequate model for virulence of serovar 5 strain of G. parasuis [34], the fact does not affect the relevance of the reported data because the mechanism was studied, which may be independent from the virulence of G. parasuis. In this study, the results of BALB/c mice infected with PCV2 and G. parasuis demonstrated that PCV2 and G. parasuis have synergistic interactions in pathology and PCV2 infection can increase G. parasuis propagation in the lungs.…”
Section: Discussionmentioning
confidence: 99%
“…To date, 15 serotypes of G. parasuis have been identified based on the Kielstein-Rapp-Gabrielson serotyping scheme [3]. Serotype 5 is the most prevalent serotype, and can be used as a virulence marker for G. parasuis infection [4]. Previous research has reported that G. parasuis can invade the central nervous system through the blood-brain barrier (BBB), resulting in meningitis [5].…”
Section: Introductionmentioning
confidence: 99%